On the Possibility of a Biblical Doctrine of the Trinity: A Review Essay - Butner, D. Glenn (The Evangelical quarterly, 2024)
A series of recently published books yield great potential for a biblical doctrine of the Trinity. I begin by showing the difficulty inherent in connecting some earlier research in biblical studies to a doctrinal articulation of the Trinity. The doctrine of the Trinity includes ontological elements, a wide range of concepts like consubstantiality and eternal generation, and a conviction that the Trinity is an accurate depiction of the God who reveals himself across the biblical canon. I then draw on six recent works on the Trinity or Christology and Scripture to note new developments related to doctrine and to offer suggested connections with historical and systematic theology. Authors discussed include Michael Bird, Ruben Bühner, Denis Farkasfalvy, Brandon Smith, Christopher Seitz, R. B. Jamieson, and Tyler Wittman.